2019
DOI: 10.1186/s12889-019-6715-3
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviors and anxiety among children, adolescents and adults: a systematic review and meta-analysis

Abstract: Background Although the number of studies examining the relationships between sedentary behaviors (SB) and anxiety is growing, an overarching evidence, taking into account children, adolescents, and adults as well as different types of SB and different categories of anxiety outcomes, is still missing. Thus, this systematic review and meta-analysis aimed at obtaining a comprehensive overview of existing evidence. Methods A search in the following databases: PsycINFO, Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 116 publications
(118 reference statements)
2
31
0
1
Order By: Relevance
“…In general, studies of the association between sedentary behaviour and mental distress in adolescents have mainly used self-report measurements for sedentary behaviour, and the results from these studies commonly show sedentary behaviour to predict higher levels of mental distress 6 19 54–56. A review found only evidence for a significant association between self-reported sedentary time and depression among adolescents, while anxiety and overall psychological distress was considered inconclusive 5.…”
Section: Discussionmentioning
confidence: 99%
“…In general, studies of the association between sedentary behaviour and mental distress in adolescents have mainly used self-report measurements for sedentary behaviour, and the results from these studies commonly show sedentary behaviour to predict higher levels of mental distress 6 19 54–56. A review found only evidence for a significant association between self-reported sedentary time and depression among adolescents, while anxiety and overall psychological distress was considered inconclusive 5.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intensity or dosage of standing for optimal benefit in adults is still unclear [14,15]. In children, excessive sedentary behaviour has been associated with increased cardiometabolic risk factors, obesity, anxiety, and depressive symptoms [5,16,17,18,19]. It has also been found that prolonged sitting is associated with the increased prevalence of musculoskeletal symptoms in children and adolescents [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…While these studies provide some support for our ndings it is important to recognise that total ST as reported in our compositional analysis is a different measure than screen time, screen time can occur in non-sedentary postures (74), and high ST is largely independent of screen time (75). It is unclear whether total ST (25) or speci c types of ST are more strongly related to mental health outcomes (76). To address this, future studies should employ methodologies such as ecological momentary assessment or device-based pattern recognition approaches to identify speci c types of sedentary behaviours (76), which may provide a more precise picture of the compositional relationships between activity behaviours and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Youth sedentary time (ST) is signi cantly associated with depression and psychological wellbeing (22,24), while a recent meta-analyses reported small but signi cant associations between overall ST and anxiety (25). Time spent using screens (e.g., TV viewing, video gaming, computer use) has different associations with health than overall ST (25), and among youth there is moderately-strong and moderate evidence for screen time associations with depression and quality of life, respectively (19). Further, unfavourable behavioural conduct, poor self-esteem, and low social support are associated with screen use in youth (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%